2019
DOI: 10.15252/embj.2019101552
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxidation of mitochondrial peroxiredoxin limits H 2 O 2 ‐induced cell death in yeast

Abstract: Hydrogen peroxide (H2O2) plays important roles in cellular signaling, yet nonetheless is toxic at higher concentrations. Surprisingly, the mechanism(s) of cellular H2O2 toxicity remain poorly understood. Here, we reveal an important role for mitochondrial 1‐Cys peroxiredoxin from budding yeast, Prx1, in regulating H2O2‐induced cell death. We show that Prx1 efficiently transfers oxidative equivalents from H2O2 to the mitochondrial glutathione pool. Deletion of PRX1 abrogates glutathione oxidation and leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 68 publications
1
57
0
2
Order By: Relevance
“…fluorescent protein have previously been used to gain mechansitic insight into glutaredoxin catalysis in vitro 18 , as well as to dynamically monitor the redox state of the intracellular glutathione pool 44,45 . Recently, we successfully established fusion constructs between redox-sensitive green-fluorescent protein 2 (roGFP2) and peroxidases for monitoring their catalytic mechanism and inactivation in living cells 46,47 . We thus asked if roGFP2 fusion constructs could also be adapted for the noninvasive assessment of Grx structure-function relationships inside living cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…fluorescent protein have previously been used to gain mechansitic insight into glutaredoxin catalysis in vitro 18 , as well as to dynamically monitor the redox state of the intracellular glutathione pool 44,45 . Recently, we successfully established fusion constructs between redox-sensitive green-fluorescent protein 2 (roGFP2) and peroxidases for monitoring their catalytic mechanism and inactivation in living cells 46,47 . We thus asked if roGFP2 fusion constructs could also be adapted for the noninvasive assessment of Grx structure-function relationships inside living cells.…”
Section: Resultsmentioning
confidence: 99%
“…In our roGFP2 assays we choose to use H 2 O 2 to initiate GSSG formation. Whilst yeast do not harbor any bona fide glutathione peroxidase, it was recently shown that GSH and/or Grx can reduce both 1-Cys and typical 2-Cys peroxiredoxins thereby leading to GSSG production 42,46,47,49,50 . Furthermore, GSSG was shown to readily accumulate in Δglr1 cells following H 2 O 2 treatment 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, knockdown of TOPK inhibits Prx1 (Ser-32) phosphorylation and thereby induces apoptosis that benefits skin cancer therapy [ 62 ]; indeed, knockout or mutation of TOPK leads to the phosphorylation of Prx1 and significantly increases H2O2. The ability of cells to tolerate oxidative stress is ultimately decreased, and this triggers apoptosis [ 63 ]. Taken together, these findings indicate that targeting TOPK is efficacious for cancer drugs resistance and, therefore, induces cell apoptosis.…”
Section: Topk Induces Apoptosis Resistance In Tumor Cellsmentioning
confidence: 99%
“…Recently, it was reported that as human PRXD6, targeted to the yeast mitochondrial matrix, elicited glutathione disulfide (GSSG) formation upon treatment of cells with H 2 O 2 [32]. Because yeast lack GSTP1, it was suggested that other enzymes may re-activate the peroxidase activity of PRDX6.…”
Section: Discussionmentioning
confidence: 99%